Immediate Effect of Hoof Trimming on Hoof and Thoracic Joint Angles in Mangalarga Mares - Antonioli, Marina Lansarini [UNESP] (2023)
It is important to understand the effects of hoof trimming on hoof and limb conformation to maximize its benefits on the health of the appendicular skeleton of horses, thus promoting improvements in athletic performance and sporting longevity with regard to athletic horses. There is little information on possible changes in the angulation of the thoracic limb joints after hoof trimming and correlations between the angulation of the thoracic limb joints with hoof measurements. To that purpose, nineteen Mangalarga mares received routine hoof trimming. Visual recordings (photographs) were taken before and after the procedure. Differences (p < 0.05) were found in hoof length, toe angle, heel angle, medial heel height, and metacarpophalangeal angle. Before trimming, correlations were found between frog length and scapulohumeral angle (SH) (r = −0.457; p = 0.049), and between toe length and shoulder-ground angle (SG) (r = −0.553; p = 0.049). A correlation was also seen between the distance from the frog to the lateral wall and the SH angle (r = 0.690; p = 0.001). After trimming, there was a correlation between humeroradial (HR) and SH joint angles (r = 0.669; p = 0.002), and the SG and SH angles (r = 0.488; p = 0.034). This study showed an immediate effect of trimming on the toe angle and heel angle and on the metacarpophalangeal joint angle, in addition to correlations between the hoof and proximal joint angles, following trimming, thus evidencing the relevance of trimming not only in hoof morphology, but also in the conformation of the appendicular skeleton of horses.